Lower plasma testosterone or dihydrotestosterone, but not estradiol, is associated with symptoms of intermittent claudication in older men - Yeap, B.; Alfonso, Helman; Chubb, S.; Handelsman, D.; Hankey, G.; Golledge, J.; Flicker, L.; Norman, P. (2013)
Objective In men, testosterone (T) levels decline with age, and lower T predicts all-cause and cardiovascular mortality. However, the associations of T and its metabolites, dihydrotestosterone (DHT) and estradiol (E2), with symptomatic peripheral arterial disease remain unclear. We assessed associations of T, DHT and E2 with lower limb intermittent claudication in older men. Design Cross-sectional study. Participants Community-dwelling men aged 70-89 years resident in Perth, Western Australia. Measurements Intermittent claudication was ascertained by the Edinburgh Claudication Questionnaire. Early morning, plasma T, DHT and E2 were assayed using liquid chromatography-tandem mass spectrometry. Results There were 268 men with intermittent claudication and 2435 without claudication or any leg pain. Men with nonspecific leg pain (n = 986) were excluded. After adjusting for age, smoking, BMI, waist/hip ratio, hypertension, dyslipidaemia, diabetes, creatinine and prevalent cardiovascular disease (CVD), higher T was associated with reduced risk of having claudication (per 1 SD increase, odds ratio [OR] = 0·80, 95% confidence interval [CI] = 0·69-0·94, P = 0·006; quartiles, Q4/Q1, OR = 0·54, 95% CI = 0·36-0·81). Higher DHT was associated with reduced risk of having claudication (per 1 SD increase, OR = 0·86, 95% CI = 0·73-1·00, P = 0·048; Q4/Q1, OR = 0·64, 95% CI = 0·43-0·95). E2 was not associated with claudication (per 1 SD increase, OR = 0·96, 95% CI = 0·83-1·11, P = 0·565; Q4/Q1, OR = 0·88, 95% CI = 0·60-1·29). Conclusions Lower T or DHT levels, but not E2, are associated with symptoms of intermittent claudication in older men. Reduced exposure to androgens may represent a causal factor or biomarker for symptomatic peripheral arterial disease. Further studies are needed to examine underlying mechanisms and evaluate therapeutic options in ageing men. © 2013 John Wiley & Sons Ltd.